2020
DOI: 10.1155/2020/5194780
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Nanoparticles That Result in Improved Cancer Targeting

Abstract: The therapeutic efficacy of drugs is dependent upon the ability of a drug to reach its target, and drug penetration into tumors is limited by abnormal vasculature and high interstitial pressure. Chemotherapy is the most common systemic treatment for cancer but can cause undesirable adverse effects, including toxicity to the bone marrow and gastrointestinal system. Therefore, nanotechnology-based drug delivery systems have been developed to reduce the adverse effects of traditional chemotherapy by enhancing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(136 citation statements)
references
References 129 publications
2
134
0
Order By: Relevance
“…The zeta potential also provides useful data for particle assessment in terms of cellular uptake, biodistribution and interaction with other biological environments [59]. The PU NP were characterized by positive low values of the zeta potential, 32 mV for empty PU NP and 35 mV for ABZ-PU NP thus showing good stability and cell penetrability as well as a low capacity to activate the immune system [49]; positively charged particles have enhanced electrostatic interactions with the negatively charged cell membrane [60] which favor their internalization, as opposed to negatively charged or neutral particles which slow down the diffusion of the active drug into the cell matrix [54,61]. In addition, negatively charged NP are strongly retrieved by the RES system [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The zeta potential also provides useful data for particle assessment in terms of cellular uptake, biodistribution and interaction with other biological environments [59]. The PU NP were characterized by positive low values of the zeta potential, 32 mV for empty PU NP and 35 mV for ABZ-PU NP thus showing good stability and cell penetrability as well as a low capacity to activate the immune system [49]; positively charged particles have enhanced electrostatic interactions with the negatively charged cell membrane [60] which favor their internalization, as opposed to negatively charged or neutral particles which slow down the diffusion of the active drug into the cell matrix [54,61]. In addition, negatively charged NP are strongly retrieved by the RES system [61].…”
Section: Discussionmentioning
confidence: 99%
“…The PU NP were characterized by positive low values of the zeta potential, 32 mV for empty PU NP and 35 mV for ABZ-PU NP thus showing good stability and cell penetrability as well as a low capacity to activate the immune system [49]; positively charged particles have enhanced electrostatic interactions with the negatively charged cell membrane [60] which favor their internalization, as opposed to negatively charged or neutral particles which slow down the diffusion of the active drug into the cell matrix [54,61]. In addition, negatively charged NP are strongly retrieved by the RES system [61]. An increase of the zeta potential values of the drug-loaded nanoparticles compared to empty ones could be attributed to the adsorption of the drug to the NP's surface [62]; however, in our experiment the measured values of the zeta potential for the two types of PU NP are very close to each other thus suggesting that ABZ adsorption to the NP surface through hydrogen bonds was negligible.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that 68 GaAuNPBBN has a strong internalization in prostate cancer PC3 cells, within 3-5 h of incubation, being mainly concentrated in the cytoplasmic fraction. Blockade experiments performed in PC3 and in LNCaP cell lines with monomeric BBN (7)(8)(9)(10)(11)(12)(13)(14) showed a significant reduction in the cellular internalization of 68 GaAuNPBBN. Analogous results were observed in blockade experiments with LUG for 68 GaAuNPLUG in LNCaP cells.…”
Section: Gallium-67/gallium-68mentioning
confidence: 95%
“…In fact, for some of them (e.g., quantum dots), their inherent toxicity is a potential drawback but for many others (e.g., iron oxide and AuNPs) toxicity issues are less relevant. Nanoparticle biodistribution can vary greatly depending on the type and size of the particle, as well as on their surface chemistry [12,13]. For imaging and/or therapy of cancer, the selective delivery of drugs or radionuclides into the tumour tissues is of paramount importance.…”
Section: Gold Nanoparticles For Biomedical Applicationsmentioning
confidence: 99%
“…Many of the current nanomedicines, used for solid tumor treatment, accumulate in tumors due to the EPR effect. A thorough knowledge of the physical properties (e.g., size, surface charge, shape, and mechanical strength) and chemical attributes of nanoparticles facilitates their application in biomedicine [55]. Specifically, nanoparticles in the range 10-100 nm can passively target tumors by freely passing through large pores (40 nm to 1 um in size) and achieve higher intra-tumoral accumulation [56] due to the highly permeable blood vessels provoked by the rapid and defected angiogenesis and dysfunctional lymphatic drainage [57].…”
Section: Design Of Ncps Nano-formulationsmentioning
confidence: 99%